Electrophoretic mobility of cardiac myosin heavy chain isoforms revisited: application of MALDI TOF/TOF analysis - Arnostova, Petra; Jedelsky, Petr L; Soukup, Tomáš; Zurmanova, Jitka (Journal of biomedicine & biotechnology, 2011)
The expression of two cardiac myosin heavy chain (MyHC) isoforms in response to the thyroid status was studied in left ventricles (LVs) of Lewis rats. Major MyHC isoform in euthyroid and hyperthyroid LVs had a higher mobility on SDS-PAGE, whereas hypothyroid LVs predominantly contained a MyHC isoform with a lower mobility corresponding to that of the control soleus muscle. By comparing the MyHC profiles obtained under altered thyroid states together with the control soleus, we concluded that MyHCα was represented by the lower band with higher mobility and MyHCβ by the upper band. The identity of these two bands in SDS-PAGE gels was confirmed by western blot and mass spectrometry. Thus, in contrast to the literature data, we found that the MyHCα possessed a higher mobility rate than the MyHCβ isoform. Our data highlighted the importance of the careful identification of the MyHCα and MyHCβ isoforms analyzed by the SDS-PAGE.
Keywords: Ventricular Myosins; Electrophoresis, Polyacrylamide Gel; sekvenční seřazení; elektroforéza v polyakrylamidovém gelu; Molecular Sequence Data; Rats, Inbred Lew; molekulární sekvence - údaje; Female; Blotting, Western; Hypothyroidism; krysa rodu Rattus; zvířata; těžké řetězce myosinu; Myosin Heavy Chains; protein - isoformy; Amino Acid Sequence; Protein Isoforms; hypotyreóza; ženské pohlaví; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Male; Sequence Alignment; potkani inbrední LEW; Hyperthyroidism; Rats; komorové myosiny; Animals; western blotting; mužské pohlaví; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; hypertyreóza; sekvence aminokyselin